Development Of Accelerated Stability Protocol For Sildenafil Tablets A European Perspective Review - SUKHDEV SINGH,; JASBIR SINGH, (International Journal of Pharma and Bio Sciences, 2010)
Frequently, the goal of a pharmaceutical company is to develop a globally acceptable registration stability protocol. A sound stability protocol not only eliminates unnecessary testing but also reduces manufacturing needs, cost and time. In this article considerable issues related to development of stability protocol such as type, size and number of batches, type, size and sources of containers and closures, container closures orientation, sampling plan, storage conditions, test time points, test parameters, test methods, acceptance criteria and the applicability of statistical methods for the analysis of stability data is discussed. The aim of this paper is to develop and outline accelerated stability protocol for Sildenafil tablets acceptable for registration in Europe and highlight some of the considerations that must be made before the execution of actual stability study.